The Effect of Storyjumper on Students’ Vocabulary Comprehension - Putu Cleo Chintya Rossa Devi (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
This study is a quasi-experimental research which aimed to investigate whether there is significant effect of using story jumper on 2nd grade students’ vocabulary comprehension in SDN 1 Semarapura Kangin. The population if this study involved 30 students from each class that was A class that was being the control class and B class that was be the experimental class. The result shows that there is significant difference of the post-test achievement between experimental group and control group proved with T =3.05, Df = 90, and sig. 0.04 (p<0.05). That means there is significant effect of effect of using story jumper on 2nd grade students’ vocabulary comprehension.